The handbook of global interventions in communication theory - Miike, Yoshitaka; Yin, Jing 1974- (New York, NY Routledge, 2022)
Moving beyond the U.S.-Eurocentric paradigm of communication theory, this handbook broadens the intellectual horizons of the discipline by highlighting underrepresented, especially non-Western, theorists and theories, and identifies key issues and challenges for future scholarship. Showcasing diverse perspectives, the handbook facilitates active engagement in different cultural traditions and theoretical orientations that are global in scope but local in effect. It begins by exploring past efforts to diversify the field, continuing on to examine theoretical concepts, models, and principles rooted in local cumulative wisdom. It does not limit itself to the mass-interpersonal communication divide, but rather seeks to frame theory as global and inclusive in scope. The book is intended for communication researchers and advanced students, with relevance to scholars with an interest in theory within information science, library science, social and cross-cultural psychology, multicultural education, social justice and social ethics, international relations, development studies, and political science"--
Includes bibliographical references and index (501-515)
Description based on print version record and CIP data provided by publisher.
Keywords: Information theory in the social sciences; Information theory; Communication -- Social aspects